Catastrophic primary antiphospholipid syndrome. - Casanova, Paula (2003)
Catastrophic antiphospholipid syndrome develops in a minority of patients with antiphospholipid syndrome, and is characterized by acute thrombotic microvasculopathy with multiorganic involvement (three or more organs). The aetiology is unknown, the diagnosis is complex, and the treatment is empiric, mortality may approach 50%. The authors present a clinical case of catastrophic antiphospholipid syndrome, diagnosed in a patient with abdominal pain and severe respiratory failure.